2022
DOI: 10.1186/s12884-021-04357-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial health in pregnancy and postpartum among women living with - and without HIV and non-pregnant women living with HIV living in Nordic countries – Results from a longitudinal survey study

Abstract: Background The success of antiretroviral therapy has normalized pregnancy among women living with HIV (WWH) with a very low risk of perinatal transmission of HIV. Despite these advances, WWH still face complex medical and psychosocial issues during pregnancy and postpartum. The aim of this study was to assess differences in psychosocial health outcomes between pregnant WWH, non-pregnant WWH, and pregnant women without HIV, and further identify factors associated with probable depression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…These include commonly investigated experiences such as depression, anxiety, 'stress' [4] and 'distress' [5,6] as well as less commonly reported 'wellbeing' [7][8][9], 'emotional disorders' [10], symptoms of PTSD (Post Traumatic Stress Disorder) [11][12][13], suicidal ideation [14], mood instability [15], anger [16] and intolerance of uncertainty [17]. These experiences have been differentiated with regard to the 'antenatal' and 'postnatal' time periods, or both [18]. Some of the Collection papers refer specifically to the adverse experiences of pregnancy loss or bereavement [19], domestic violence [20] or being displaced during genocidal violence [21].…”
Section: Issues Of Definitionmentioning
confidence: 99%
“…These include commonly investigated experiences such as depression, anxiety, 'stress' [4] and 'distress' [5,6] as well as less commonly reported 'wellbeing' [7][8][9], 'emotional disorders' [10], symptoms of PTSD (Post Traumatic Stress Disorder) [11][12][13], suicidal ideation [14], mood instability [15], anger [16] and intolerance of uncertainty [17]. These experiences have been differentiated with regard to the 'antenatal' and 'postnatal' time periods, or both [18]. Some of the Collection papers refer specifically to the adverse experiences of pregnancy loss or bereavement [19], domestic violence [20] or being displaced during genocidal violence [21].…”
Section: Issues Of Definitionmentioning
confidence: 99%
“…The actions that result from these decisions may have either favorable or unfavorable effects on a person's health, but they nonetheless form a general pattern of healthy habits that make up a lifestyle (Cockerham, 2013;Cockerham, 2005). In the postpartum settings, we tried to emerge some indicators about healthy lifestyle needs among post-partum mother namely healthy diet, healthy body weight, healthy physical activity, and healthy psychological management (Gila-Díaz et al, 2021;Moseholm et al, 2022;Teh et al, 2021) (Figure 1).…”
Section: Needsmentioning
confidence: 99%
“…Maternal loneliness during pregnancy and the postpartum period is associated with several health issues for the mother and her child. Various studies showed a positive correlation between loneliness and depression during pregnancy across countries [5][6][7][8][9][10]. In addition, maternal loneliness is associated with life dissatisfaction and pair-relationship dissatisfaction [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated loneliness during pregnancy and the postpartum period utilizing observational methods based on self-report measures, such as standard questionnaires [8] and interviews [16]. For example, Perzow et al in [5] used self-report questionnaires to discern symptoms of depression and anxiety, loneliness, and COVID-19-related adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation